2019
DOI: 10.1002/jcc.25864
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction of Ni(I)‐catalyst for hydrosilylation of pyridine and quinoline

Abstract: Catalytic synthesis of dihydropyridine by transition‐metal complex is one of the important research targets, recently. Density functional theory calculations here demonstrate that nickel(I) hydride complex (bpy)NiIH (bpy = 2,2′‐bipyridine) 1 is a good catalyst for hydrosilylation of both quinoline and pyridine. Two pathways are possible; in path 1, substrate reacts with 1 to form stable intermediate Int1. After that, N3─C1 bond of substrate inserts into Ni─H bond of 1 via TS1 to afford N‐coordinated 1,2‐dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Considering that the Ni hydride complex is an important intermediate in many Ni-catalyzed processes, we calculated the reaction of h-Int with CO 2 . As shown in Figure b, h-Int reacting with CO 2 to generate the intermediate i-Int1-1 (a precursor for the formation of HCOO – ) via the transition state i-TS1 requires overcoming a free energy barrier of 11.4 kcal/mol.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Considering that the Ni hydride complex is an important intermediate in many Ni-catalyzed processes, we calculated the reaction of h-Int with CO 2 . As shown in Figure b, h-Int reacting with CO 2 to generate the intermediate i-Int1-1 (a precursor for the formation of HCOO – ) via the transition state i-TS1 requires overcoming a free energy barrier of 11.4 kcal/mol.…”
Section: Resultssupporting
confidence: 85%
“…32,65 Since the concentration of protons is much lower than that of CO 2 in the reaction system, the formation of h-Int should be restrained, only generating a small amount of H 2 . Considering that the Ni hydride complex is an important intermediate in many Ni-catalyzed processes, 66 we calculated the reaction of h-Int with CO 2 . As shown in Figure 8b, h-Int reacting with CO 2 to generate the intermediate i-Int1-1 (a precursor for the formation of HCOO − ) via the transition state i-TS1 requires overcoming a free energy barrier of 11.4 kcal/ mol.…”
Section: Resultsmentioning
confidence: 99%
“…In combination with the experimental results, density functional calculations have been widely used to elucidate reaction mechanisms of Ni-catalyzed hydroelementation reactions. In addition to the OA/MI and CMD mechanisms, recent density functional studies showed that hydroarylation and hydroalkenylation of alkenes and alkynes catalyzed by Ni complexes proceed via a ligand-to-ligand H-transfer (LLHT) pathway. In the LLHT pathway, aromatic C–H bond activation occurs by direct H-transfer from the arene to alkene/alkyne; subsequently, the hydroarylation product is reductively eliminated. The alkene/alkyne plays the role of a hydrogen acceptor in the LLHT mechanism similar to what a Lewis base does in the CMD mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when the reaction was performed by adding 5 mol% of 5 as catalyst, only 15 % NMR yield of the desired product was obtained in reactions proceeding for 18 h (Scheme 3, F ). This result suggests that the dihydrosilyl‐Ru species 5 is not an active (or off‐cycle) species in this reaction, [18,24] unless it proves to be an irreversibly formed off‐cycle species that is detrimental to catalytic progress.…”
Section: Resultsmentioning
confidence: 97%
“…This yields the N-silylated product 3 a with regeneration of the active catalyst I with an energy barrier of 30.2 kcal/mol (TS-IV). [17][18]24] In path B, complex II undergoes the six-member transition state TS-II' for the hydride transfer with a barrier of 33.6 kcal/ mol. Within TS-II' one H is transferred from Ru to silane and a H atom transfers from silane to carbon of the quinolone to form intermediate IV.…”
Section: Resultsmentioning
confidence: 99%